The Disnarrated and Denarrated in Eugene O’Neill’s The Iceman Cometh - Pirnajmuddin, Hossein; Mousavi, Maryamossadat (Text Matters: A Journal of Literature, Theory and Culture, 2024)
Drawing on the notions of “disnarration” (telling what did/does not occur) and “denarration” (cancelling or negating what has occurred) as theorized by, respectively, Gerald Prince and Brian Richardson, this paper examines the narrative structure of Eugene O’Neill’s The Iceman Cometh (1939). We focus on textual details to explain how the disnarrated and the denarrated in O’Neill’s play are mostly manipulated as narrative as well as thematic devices to mark the consoling and soothing illusions of the “pipe dreams” which give meaning to the lives of the bar’s regulars. Central to our analysis is how the self-deluded tavern loafers, of whom Hickey is a paragon, resort to a whole spectrum of narrative negations because to them truth is too painful to bear. We argue that the use of disnarration and denarration by Hickey and the other characters in the play helps to create an all-protective world of non-being furnished with an illusion of safety and a false sense of contentment masking feelings of fragility and meaninglessness. These narrative features are central, whether we take Hickey to be a character who is genuinely suffering from mental illness or a cunning criminal who has killed his wife in cold blood.